Effects of periodontal therapy on white blood cell count and levels of transforming growth factor beta in serum of subjects with severe periodontitis - Leite, A C E; Carneiro, V M A; Morandini, A C; Ramos-Junior, E S; Guimaràes, M C M (Cellular and Molecular Biology, 2015)
This study aimed to investigate the effects of nonsurgical periodontal therapy on white blood cell (WBC) count and levels of transforming growth factor beta (TGF-Î²) in serum from subjects with severe periodontitis. Serum from 28 subjects with periodontitis (mean age: 34.36±6.24; 32% men) and 27 healthy controls (mean age: 33.18±6.42; 33% men) were collected prior to therapy. Blood samples were obtained from 23 subjects who completed therapy (9-12 months). A well-controlled periodontal treatment protocol was established in three stages: mechanical periodontal therapy (scaling and root planning), reinstrumentation of dental sites, and supportive periodontal therapy. Periodontal and systemic parameters such as the total number of WBCs and TGF-Î² levels, accessed by enzyme-linked immunosorbent assay (ELISA), were included. After therapy, all clinical periodontal parameters decreased (p<0.0001). There were no statistical differences in WBC count between experimental and control groups before or after therapy. However, after therapy, the mean value of lymphocytes in patients with localized aggressive periodontitis (LAgP) was statistically higher than that of patients with generalized chronic periodontitis (GCP) (p<0.0357). Additionally, TGF-Î² levels in LAgP and GCP patients were higher compared to controls before therapy (p<0.05 and p<0.01, respectively). In LAgP patients, periodontal therapy was associated with increased number of lymphocytes.